Guest Editors' Introduction Managing Organizational Security. - Lawrence Pfleeger, Shari (IEEE Security and privacy : building confidence in a networked world)
In this special issue, we focus on the challenges of managing organizational security, examining some of the nontechnical aspects of security that assure that the technology is chosen, implemented, and used appropriately and well.